Characterization of Antennas on Dielectric and Magnetic Substrates Effective Medium Approximation - Rialet, Damien; Sharaiha, Ala; Tarot, Anne-Claude; Castel, Xavier; Delaveaud, Christophe (Společnost pro radioelektronické inženýrství, 2009)
This paper presents a study of the effective medium approximation of a monopole antenna printed on either a dielectric or a magnetic substrate. Simple analytical formulas to determine the effective permeability of such an antenna have been proposed and validated. For this type of antenna as μr increases, the effective permeability will reach the value of 2 (maximum) whereas, with the dielectric substrate, the effective permittivity continues to rise when increasing εr. This shows that, for very high permeability values, we will always have a size reduction below 30%.
Keywords: Antennas on dielectric and magnetic substrates; effective medium; analytical model